The influence of physical literacy of student with different obesity levels on physical fitness: the mediating effect of MVPA - Yan, Wenjing; Nie, Mingjian; Ma, Ruisi; Guo, Qi; Li, Hongjuan (Frontiers in Public Health, 2024)
Background: Perceived physical literacy (PL) is a potential factor for improving health and physical activity, but the relationship between PL and physical fitness (PF) among college students with different obesity levels has not yet been determined.The aim of this study was to explore the correlation between PL, moderate-to-vigorous physical activity (MVPA), and PF among college students with different obesity levels.We recruited Chinese university students to complete a questionnaire and conducted a survey using the Perceived Physical Literacy Instrument Scale (PPLI-SC) and the International Physical Activity Questionnaire Short Form (IPAQ-SF). The physical fitness test data were used for data analysis. The direct and indirect impacts were analyzed using Pearson correlation and the SPSS Hayes process macro (Model 4).The study surveyed 909 boys and 1668 girls for a total of 2,577 valid questionnaires. Similarly, the MVPA and perceived PL of boys were significantly greater than those of girls (p < 0.01), but the opposite was true for the PF score. The correlation analysis showed that MVPA, perceived PL, and PF were significantly correlated (p < 0.01). For normal weight student, the results showed that the direct effect of PL on PF was still statistically significant (β = 0.076, p < 0.01) after adding MVPA; MVPA had a positive effect on PF after controlling for perceived PL (β = 0.055, p < 0.05)). Perceived PL has a positive effect on MVPA (β = 0.123, p < 0.01). The mediating effect of MVPA was notably significant, with a mediation effect percentage of 7.9%. However, it has been found that among the underweight population, there is an absence of a significant relationship between PL, PF, and MVPA (p＞0.05). Contrarily, in the overweight and obese groups, the mediating role of MVPA in the relationship between PL and PF was not statistically supported (-0.002, 0.033).For normal weight student, perceived PL has a positive impact on PF and can also be promoted by increasing the pathway of MVPA. For both underweight individuals and obese populations, further investigation is needed into methods for promoting PA and improving PF.